Génesis de la ciudadanía: mecanismo ordenador de las relaciones de fuerza y dominación - Bonilla Urbina, Marcelo (2024)
The study is a theoretical reflection aimed at understanding the dynamics of inclusion and social and cultural exclusion generated from the birth of citizenship as a means of social cohesion, political and cultural nation-state and its subsequent transformation to the present time. Specifically, this reflection is aimed al building theoretical elements in arder to understand current processes of civic exclusion that suffer mainly cultural minoríties (ethníc and national) in the context of the creation of the European Union and globalization.